Developing an IoT-based inventory management system using Node-RED: Enhancing smart factory environments - Tan, Yi Fei (2025)
The integration of the Internet of Things (IoT) within smart factory environments is revolutionizing inventory management processes to make them more efficient and responsive. This project focuses on developing a simulation-based IoT inventory management system using Node-RED to demonstrate smart factory operations such as real-time monitoring, inventory tracking, predictive maintenance, and quality control. The system integrates technologies of Node-RED, MQTT, InfluxDB, and Telegram to simulate and visualize factory activities. All data used in this simulation is generated virtually within Node-RED to mimic the behavior of a real-world manufacturing environment. This includes simulated temperature, humidity and pressure readings, electronic components movement across various stages (mounting, soldering, inspection, testing, packaging), inventory level changes, and machine runtimes. The system also features a notification mechanism via Telegram to alert factory managers in real time about key events such as high temperature, defective components, low inventory levels, and scheduled maintenance. This simulation provides a cost-effective and scalable platform for testing and visualizing IoT-based inventory management solutions. The use of Node-RED allows flexible flow-based programming so that the system is highly adaptable for educational and prototyping purposes. Additionally, real-time data tracking, automated decision- making, and visualization through the Node-RED Dashboard enable a deeper understanding of how smart factories can operate more efficiently. This project highlights the potential of IoT integration for achieving improved resource utilization, reduced downtime, and enhanced decision-making in inventory management processes. It serves as a foundation for further development toward more intelligent, connected, and automated factory systems.